Physical function assessment tools in pediatric rheumatology - Onel Karen B; Harrison Melanie J; Peterson Margaret GE; Moorthy Lakshmi; Lehman Thomas JA (BMC, 2008)
Abstract Pediatric rheumatic diseases with predominant musculoskeletal involvement such as juvenile idiopathic arthritis (JIA) and juvenile dermatomyositis(JDM) can cause considerable physical functional impairment and significantly affect the children's quality of life (QOL). Physical function, QOL, health-related QOL (HRQOL) and health status are personal constructs used as outcomes to estimate the impact of these diseases and often used as proxies for each other. The chronic, fluctuating nature of these diseases differs within and between patients, and complicates the measurement of these outcomes. In children, their growing needs and expectations, limited use of age-specific questionnaires, and the use of proxy respondents further influences this evaluation. This article will briefly review the different constructs inclusive of and related to physical function, and the scales used for measuring them. An understanding of these instruments will enable assessment of functional outcome in clinical studies of children with rheumatic diseases, measure the impact of the disease and treatments on their lives, and guide us in formulating appropriate interventions.